Hadis-Hadis tentang Perlindungan Hak Asasi Manusia - Muhammad Yasin; Abustani Ilyas; Tasbih (CV Global Research Publication, 2026)
Human rights are fundamental rights inherent to every individual that must be respected without discrimination. This study aims to explore the concept of human rights protection within the Hadith of Prophet Muhammad SAW and its relevance to contemporary society. Employing a qualitative approach through library research, primary data were sourced from the Sahih Muslim and other pertinent hadith literatures, which were then analyzed using descriptive-analytical content analysis. The results indicate that the Hadith comprehensively regulates the protection of the right to life, legal justice, security, and honor, as well as social and economic rights for vulnerable groups. These principles align with modern human rights concepts regarding justice and equality; however, they differ in their epistemological foundations, where Islam places revelation as the primary source and emphasizes a balance between rights, obligations, and moral responsibility. The implementation of these Hadith-based values remains highly relevant as an ethical framework for public policy and law enforcement to address modern global challenges, such as social inequality and the abuse of power.